Partial Domain Search Tree for Constraint-Satisfaction Problems - Sharon, Guni (Proceedings of the International Symposium on Combinatorial Search, 2015)
The traditional approach for solving Constraint satisfaction Problems (CSPs) is searching the Assignment Space in which each state represents an assignment to some variables. This paper suggests a new search space formalization for CSPs, the Partial Domain Search Tree (PDST). In each PDST node aunique subset of the original domain is considered, values are excluded from the domains in each node to insure that a given set of constraints is satisfied. We provide theoretical analysis of this new approach showing that searching the PDST is beneficial for loosely constrained problems. Experimental results show that this new formalization is a promising direction for future research. In some cases searching the PDST outperforms the traditional approach by an order of magnitude. Furthermore, PDST can enhance Local Search techniques resulting in solutions that violate up to 30% less constraints.